2015
DOI: 10.2147/cia.s72399
|View full text |Cite
|
Sign up to set email alerts
|

Bridging the digital divide in older adults: a study from an initiative to inform older adults about new technologies

Abstract: PurposeIn a society where technology progresses at an exponential rate, older adults are often unaware of the existence of different kinds of information and communication technologies (ICTs). To bridge the gap, we launched a 2-year project, during which we conducted focus groups (FGs) with demonstrations of ICTs, allowing older adults to try them out and to share their opinions. This study aimed at investigating how participants perceived this kind of initiative and how they reacted to different kinds of ICTs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
158
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 182 publications
(164 citation statements)
references
References 32 publications
3
158
1
2
Order By: Relevance
“…Two qualitative studies [52,89] using focus groups and individual interviews of 63 older adults revealed that participants perceived themselves as too old to learn certain technologies [52]. Some older adults experience anxieties and fears that they will make fatal mistakes while using technology, such as inadvertently deleting a file or breaking the device, which facilitates a self-perception as being incapable of utilizing technology [34,70,90]. While this low technical confidence does not to hinder effectiveness or efficiency of using technology in the general population, one study directly compared the impact of technical confidence of older adults (ages 50-69) and young adults (18)(19)(20)(21)(22)(23)(24)(25)(26)(27) on technology usage and found older adults' low technical confidence hindered both efficiency and effectiveness [37].…”
Section: Dispositional Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two qualitative studies [52,89] using focus groups and individual interviews of 63 older adults revealed that participants perceived themselves as too old to learn certain technologies [52]. Some older adults experience anxieties and fears that they will make fatal mistakes while using technology, such as inadvertently deleting a file or breaking the device, which facilitates a self-perception as being incapable of utilizing technology [34,70,90]. While this low technical confidence does not to hinder effectiveness or efficiency of using technology in the general population, one study directly compared the impact of technical confidence of older adults (ages 50-69) and young adults (18)(19)(20)(21)(22)(23)(24)(25)(26)(27) on technology usage and found older adults' low technical confidence hindered both efficiency and effectiveness [37].…”
Section: Dispositional Characteristicsmentioning
confidence: 99%
“…When there are no clear benefits to its utilization, such as maintaining autonomy and independence, the older adult is far more likely to disengage from or avoid technology [9,37,47,50,52,75,82,91]. Lack of interest may be due in part to: a perception that it does not fulfill a salient need [52]; an indirect reflection of other personal factors, such as anxiety, fear, or lack of self-efficacy [90]; or simply that time is better spent doing something else [52]. Some older adults report reaching a "technological plateau", at which there is no perceived utility in adapting again to new technologies [92].…”
Section: Attitudes Towards and Motivations To Use Technologymentioning
confidence: 99%
“…Older adults believe that learning to use new technologies is important to avoid feeling alienated from society [12]. They may also feel unable to cope with technology today [38].…”
Section: User-centred Design Of Assistive Exoskeletonsmentioning
confidence: 99%
“…In addition, relatively little is known about older adults' opinions on using exoskeletons, or assistive robots in general, for daily tasks in the home [10,11]. Issues with adoption and acceptance may be expected, since some older adults are slower to adopt and use new technologies compared to younger people [12]. Therefore, research providing user insights may be useful to help understand and optimise the acceptance and adoption of such devices by older adults.…”
Section: Introductionmentioning
confidence: 99%
“…Even, there are some studies focused on especially the acceptance of users in using their mobile phones to monitor health status [88,89]. Nonetheless, assistive technologies especially for cognitive rehabilitation still need to overcome significant barriers in order to be adopted by older people including: privacy, functionality, suitability for daily use, perceived need and usefulness, costs, accessibility, fear of dependence, lack of training and stigmatisation by using technologies specifically targeting older users ('gerontechnology') [90,91].…”
Section: Limitations Of Smart Technologies For Daily Livingmentioning
confidence: 99%